Making of the 1944 Education Act. - Barber, Michael (Cassell education., 2000)
The 1944 Education Act was a crucial piece of British legislation - one of the most important this century. It was passed against a background of war and growing popular demand for social reform. It provided a framework for the education service which remained largely intact for almost fifty years. Since 1988, however, with the introduction of a National Curriculum and competition between schools, the workings of the Act have been largely dismantled. In The Making of the 1944 Education Act, Michael Barber presents a lively evaluation of the Act - its background, passage and effect - fifty year.